Designing the prototype of smart athletes recording equipment based on internet of things using the arduino board - Abdavi, F.; Khodadadi, M. R.; Heidari Param, A.; Pashaie, S. (Journal of Advanced Sport Technology, 2019)
Nowadays recording the performances and body activities of the athletes during the exercises and the matches have noticeable importance which is the reason for growth of the sports wearable`s technology, for the past few years. Accordingly, we designed new wearable equipment on the basis of internet of things, using Arduino Boards and different kind of sensors for recording the performance and physical activities of the athletes. The process data of the sensors are available in real time and could be displayed in the PC through the internet connection which makes the coach capable of analyzing the performance of the athlete during or after the activity. The weight of this equipment is less than 100 gr and works with a frequency of 5 Hz (the data will be updated every 200 ms). The advantages of the designed equipment comparing to similar imported ones are the smaller size and the less ultimate cost.